Study on production of Cocos Nucifera L. (coconut) shell as a bio-briquette - Nor Khairiyah Azra Kamiran (2017)
Charcoal is the principle cooking or fuel that widely used as households rural. This study covers the production of briquette from coconut shell as a solid bio fuel. The solid bio-briquette has been produced by coconut shell by adding different binding agents. Investigations was undertaken to produce fuel briquette from coconut shell powder waste with two different binder namely molasses and starch at the ratio 100:0, 80:20, 60:40, 50:50 and 40:60. Physical properties of the bio-briquette is compressive strength, impact testing and durability time to briquette ignite testing showed rapidly improvement with increasing amount of binder. Other parameter of sample that will be determined is the effect of different shape of bio-briquette such as cylinder, circle (ball shape) and square with uniform composition of CS powder: binder, 80:20. This studied was conducted to determine the mechanical properties and durability of the bio-briquette. Analysis and compressive test has been conducted to study the characteristics of produced bio-briquette. Furthermore, the time of briquette to ignite has been determined to estimate the combustion process for biofuel. The mechanical properties and impact resistance of briquette can be improved with the suitable ratio of coconut shell powder and binder was applied. The testing for mechanical properties and impact test was conducted to investigate the suitable binder composition in bio-briquette production. Usage of binder is an common practice with improving quality of pressure apply in production of bio-briquette 2kg loaded into a cylindrical shape diameter 12.5mm, high 8mm was prepared. Mechanical properties was tested by Universal Testing Machine (UTM), 9 sample was prepared and 5 sample can be tested due to another 4 sample not completely dry because unforeseen event. Impact testing was studied the percentage of weight losses of bio-briquette when the sample drop onto the floor at 1.83cm. Shatter resistance index of sample also can calculated, and from this method the maximum strength of bio-briquette was predicted. Final result of experiment testing was showed the more strength bio-briquette is bio-briquette contain 20% of starch binder that showed low weight loss when the sample was dropped from the height and it sample has higher shatter resistance index. In durability testing whereas the sample’s time to ignite, it found that bio-briquette with molasses more easily to ignite compared to bio-briquette with starch. Different geometry of bio-briquette was effected the time to bio-briquette ignite. The shorter time take to bio-briquette ignite is ball shape sample due to the surface contact on the flame.